(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This work sought to reveal ways of doing, intersections, boundaries and branches of an experience of art and curation: a_ponte: university theater scene, from the possibilities of dialogue between fields of pedagogy, scenic arts and cultural management, aiming beyond the construction of memory and sharing, the possibility of possible futures for an ongoing experience, deeply affected and impacted by the current situation, the scenario of the COVID-19 pandemic in 2020.